2011
DOI: 10.1515/jpm.2011.030
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin versus dinoprostone vaginal insert for induction of labor after previous cesarean section: a retrospective comparative study

Abstract: Both tested methods appear to be equally safe and effective for induction of labor in women with a previous cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is generally believed that short intervals increase the risk of rupture, but there is no consensus about the optimal period: some authors suggest a minimum of 18 months, whereas other authors propose at least 24 months to decrease the risk. In contrast, Gomez et al did not identify any interval time to reduce the risk of uterine rupture/dehiscence [18].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is generally believed that short intervals increase the risk of rupture, but there is no consensus about the optimal period: some authors suggest a minimum of 18 months, whereas other authors propose at least 24 months to decrease the risk. In contrast, Gomez et al did not identify any interval time to reduce the risk of uterine rupture/dehiscence [18].…”
Section: Discussionmentioning
confidence: 92%
“…The included studies did not control for these potential confounding factor. More importantly, the optimal method of induction in women attempting vaginal delivery after previous cesarean section is far for being clearly defined [6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent prospective studies had evaluated dinoprostone for labor induction in patients with previous CS and demonstrated a comparable successful vaginal rate. On the other hand, Gómez and colleagues [30] conducted a retrospective study to compare the efficacy and safety profile between the dinoprostone vaginal pessary and oxytocin for labor induction in 526 pregnant women with prior CS. They revealed no significant difference between the two methods in the rates of vaginal delivery (64.4% for the dinoprostone group and 65.9% for the oxytocin group, P = 0.71).…”
Section: Commentsmentioning
confidence: 99%
“…The greatest concern for these patients is an increased risk of uterine rupture and maternal-fetal morbidity. While the risk of uterine rupture during TOLAC in patients with one prior LTCD is commonly cited as 0.5-1%, and in some reports as high as 1.7%, the risk in women with more than one previous CD is reported to be anywhere between 0.9 and 3.7% [2,[30][31][32][33][34][35][36][37]. Data on composite maternal morbidity in TOLAC and VBAC with two prior CDs is even more variable.…”
Section: Contraindications and Relative Contraindications To Tolacmentioning
confidence: 99%
“…Conversely, several factors are associated with a decreased chance a successful VBAC (Box 5). First, a shorter interdelivery interval has been associated with a reduced chance of achieving VBAC and a potentially increased risk of uterine rupture [33,69,70]; ideally, a waiting period of between 18 and 24 months is recommended before attempting TOLAC [71,72]. Next, although several studies have reported decreased VBAC rates in women attempting TOLAC at >40 weeks of gestation, there is no consensus on whether uterine rupture rates are increased in this population [73][74][75][76].…”
Section: Perspective -Clark Carver and Hankinsmentioning
confidence: 99%